👤

Lucrați în perechi! Rezolvaţi în R ecuatia
a) (x-3)(x+4)-2(3x-2)=(x-4)²;
b) (x+5)(x+2)-3(4x-3)=(x-5)²;
c) x(x+2)-13=(x-3)(x+3);
d) 4x(x-1)=(2x+5)(2x-5)+1.​


Răspuns :

102533

Răspuns:

Explicație pas cu pas:

a) (x-3)(x+4)-2(3x-2)=(x-4)² <=>

+4x-3x-12-6x+4 = -8x+16 =>

-5x+8x = 16+8 => 3x = 24 => x = 24:3 => x = 8

=============

b) (x+5)(x+2)-3(4x-3)=(x-5)² =>

+2x+5x+10-12x+9 =-10x+25 =>

-5x+10x = 25-19 => 5x = 6 => x = 6/5

==============

c) x(x+2)-13=(x-3)(x+3) =>

+2x-13 = -9 => 2x = 13-9 =>

2x = 4 => x = 4:2 => x = 2

===================

d) 4x(x-1) = (2x+5)(2x-5)+1 =>

4x²-4x = 4x²-25+1 => 4x = 24 =>

x = 24:4 => x = 6